Preparation method and application of two-dimensional nano titanium carbide / nine-cobalt octasulfide heterojunction photocatalytic material

By preparing Ti3C2/Co9S8 heterojunction photocatalytic materials, the problems of narrow light absorption range and low separation efficiency of photogenerated carriers in the process of photocatalytic preparation of H2O2 by existing photocatalysts are solved, and more efficient photocatalytic performance and H2O2 production are achieved. Rate.

CN119327492AActive Publication Date: 2025-01-21HEILONGJIANG UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411444921.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-21
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

In the process of photocatalyzing the preparation of H2O2 in existing photocatalytics, the absorbance range of existing photocatalysts is mainly concentrated in the red and near-infrared light regions of visible light, and the photogenerated carrier separation efficiency is low.

Method used

The preparation method of Ti3C2/CO9S8 heterogeneous node optical catalytic material is used to form a heterogeneous structure of nano -ball and nanospinum with the heterogeneous structure of the CO9S8 matrix with the Ti3C2 powder, which enhances the separation of photogonic carriers and the transfer of electronics.

Benefits of technology

It effectively expands the visible light absorption range, improves the photocatalytic performance, enhances the selectivity and productivity of H2O2, and the catalyst can be reused.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327492A_ABST
    Figure CN119327492A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a two-dimensional nano titanium carbide / nine-cobalt octasulfide heterojunction photocatalytic material, and aims to solve the problems that in the H2O2 preparation process of an existing photocatalyst, the light absorption range is mainly concentrated in the red and near-infrared light regions of visible light, and the photon-generated carrier separation efficiency is low. The preparation method comprises the following steps: 1, sequentially adding CH3CSNH2 and NaOH into a cobalt nitrate solution, and stirring and mixing at normal temperature to obtain a Co9S8 matrix; 2, adding titanium aluminum carbide into a hydrofluoric acid solution, stirring and reacting for a long time to obtain precursor Ti3C2 powder, dispersing the precursor Ti3C2 powder into a dimethyl sulfoxide solution, and stirring and dispersing to obtain Ti3C2 powder; and 3, preparing the Ti3C2 / Co9S8 heterojunction photocatalytic material. The Ti3C2 / Co9S8 heterojunction photocatalytic material prepared by the invention can expand the absorption range of visible light, and has excellent photocatalytic H2O2 production activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a Ti3C2 / Co9S8 heterojunction photocatalytic material. Background Art

[0002] In recent years, in-depth research has been conducted at home and abroad on scientific and technological issues in the field of photocatalytic H2O preparation of H2O2, including improving photocatalytic efficiency, optimizing the utilization rate of solar energy and the response range of visible light, and improving photocatalytic reaction systems, and certain breakthroughs have been made, bringing hope for the full application of solar energy in a wider range of fields. The process of photocatalytic H2O preparation of H2O2 (hereinafter referred to as "photo-production of H2O2") using semiconductor materials as photocatalysts and using sunlight or visible light as the driving force has mild reaction conditions and can directly use sunlight as an energy source to participate in chemical reactions. Its application potential in the field of synthetic H2O2 has gradually emerged. The raw materials of this process are all taken from nature, which is green, safe and energy-saving, and is very suitable for the preparation of low-concentration H2O2 required for the oxidation of fine small molecules. Therefore, the exploration of more efficient semiconductor-based photocatalytic materials, and then the functionalization of other active components to produce "dual functions" or "integrated" effects has received more attention, and ultimately reflects the atomic economy of photo-production of H2O2 technology.

[0003] As a new type of two-dimensional material, MXenes have a wide light absorption range in both visible and near-infrared regions. The incident light energy is absorbed by the MXenes material and converted into heat energy to increase the system temperature, accelerate the thermodynamics and kinetics of electron transfer, and thus increase the macroscopic reaction rate. Ti3C2 is a classic MXenes material with a two-dimensional layered structure, good conductivity, and good visible light response. The chemical properties, electronic properties, and surface activity of Ti3C2 can be regulated by surface modification and ion exchange to meet the needs of different applications. Summary of the invention

[0004] The present invention aims to solve the problems that in the process of photocatalytic preparation of H2O2 by existing photocatalysts, the absorption range is mainly concentrated in the red and near-infrared light regions of visible light, while the absorption capacity for other wavelengths in the visible spectrum range is weak, and the separation efficiency of photogenerated carriers is low, and a preparation method and application of Ti3C2 / Co9S8 heterojunction photocatalytic material are provided.

[0005] The preparation method of the Ti3C2 / Co9S8 heterojunction photocatalytic material of the present invention is achieved by the following steps:

[0006] 1. Preparation of Co9S8 matrix:

[0007] Dissolve Co(NO3)2·6H2O in deionized water, stir to obtain a cobalt nitrate solution, then add CH3CSNH2 and NaOH to the cobalt nitrate solution in sequence, stir and mix at room temperature for 1.5 to 3 hours, wash the solid phase product with water, and dry to obtain a Co9S8(CS) matrix;

[0008] 2. Preparation of Ti3C2:

[0009] a. Add titanium aluminum carbide (Ti3AlC2) to a 40wt.% hydrofluoric acid solution, stir and react for 45 to 60 hours at room temperature, and wash and dry the solid phase to obtain a precursor Ti3C2 powder;

[0010] b. Dispersing the precursor Ti3C2 powder in a dimethyl sulfoxide (DMSO) solution, stirring for 20 to 30 hours, and then ultrasonically treating for 1 to 2 hours, and obtaining Ti3C2 powder after washing and drying;

[0011] 3. Preparation of Ti3C2 / Co9S8 heterojunction photocatalytic materials:

[0012] The Co9S8 matrix and Ti3C2 powder are mixed and ground to obtain a mixed powder, which is dispersed in DMSO and stirred at room temperature for 20 to 30 hours, then ultrasonically treated for 1 to 2 hours, and the reaction product is washed and dried to obtain a Ti3C2 / Co9S8 heterojunction photocatalytic material.

[0013] The application of the Ti3C2 / Co9S8 heterojunction photocatalytic material of the present invention is to use the Ti3C2 / Co9S8 heterojunction photocatalytic material to prepare H2O2 by photocatalysis of H2O.

[0014] Compared with the prior art, the preparation method and application of the Ti3C2 / Co9S8 heterojunction photocatalytic material of the present invention include the following

[0015] Beneficial effects:

[0016] 1. The Ti3C2 / Co9S8 heterojunction photocatalytic material prepared by the present invention can effectively expand the absorption range of visible light and has a wide light absorption range in both the visible light and near-infrared light regions.

[0017] 2. The Ti3C2 / Co9S8 heterojunction photocatalytic material prepared by the present invention comprises Co9S8 nanoflower balls and Ti3C2 nanosheets which are stirred and mixed to further disperse Co9S8 and Ti3C2. The Co9S8 nanoflower balls are subjected to ultrasonic treatment to form Co9S8 nanosheets which are inserted into the Ti3C2 nanosheet layer to form a heterostructure. The microstructure of the nanosheets inserted into the Ti3C2 intercalation layer accelerates the separation of photogenerated carriers and the transfer of electrons, thereby enhancing the efficiency of photocatalytic synthesis of H2O2 in water. Moreover, the morphology and structural regularity of the Ti3C2 / Co9S8 sample change with the change of Ti3C2 content.

[0018] 3. The Ti3C2 / Co9S8 heterojunction photocatalytic material prepared by the present invention has a significant restriction on the recombination of photogenerated carriers, and the constructed S-type heterojunction improves the electron transfer capacity, electron donor density and e of the composite material. - -h + The Ti3C2-5 / Co9S8 catalyst has an important role in the separation rate. The generated H2O2 concentrations in pure water and real seawater are 7.84 mM·h-1 and 7.84 mM·h-1, respectively, without using electron and proton donors. -1 ·g cat -1 and 12.5 mM·h -1 ·g cat -1 .

[0019] 4. The method for preparing the Ti3C2 / Co9S8 heterojunction photocatalytic material of the present invention has the characteristics of simple process, easy operation and low equipment requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 X-ray diffraction patterns of samples Co9S8, Ti3C2 / Co9S8, and Ti3C2. The black line in the figure is pure Co9S8 powder, the green line is Ti3C2-2 / Co9S8 composite material with a Ti3C2 mass content of 2% (TC-2 / CS), the pink line is Ti3C2-5 / Co9S8 composite material with a Ti3C2 mass content of 5% (TC-5 / CS), the blue line is Ti3C2-10 / Co9S8 composite material with a Ti3C2 mass content of 10% (TC-10 / CS), and the purple line is pure Ti3C2 powder;

[0021] Figure 2 Schematic diagram and SEM photos of the composition of samples Co9S8 and TC-5 / CS;

[0022] Figure 3The transient photocurrent response diagram of samples Co9S8, Ti3C2 / Co9S8, and Ti3C2. The black line in the figure is pure Co9S8 powder, the green line is TC-2 / CS composite material, the pink line is TC-5 / CS composite material, the blue line is TC-10 / CS composite material, and the purple line is pure Ti3C2 powder;

[0023] Figure 4 The Nyquist curves of samples Co9S8, Ti3C2 / Co9S8, and Ti3C2. The black line is pure Co9S8 powder, the green line is TC-2 / CS composite material, the pink line is TC-5 / CS composite material, the blue line is TC-10 / CS composite material, and the purple line is pure Ti3C2 powder.

[0024] Figure 5 The effect of sample Co9S8, Ti3C2 / Co9S8, and Ti3C2 content on H2O2 yield in pure water and seawater (reaction conditions: 300W Xe lamp, 0.03g photocatalyst, 50mL pure water, pH=7, 20℃). The black line in the figure is pure Co9S8 powder, the green line is TC-2 / CS composite material, the pink line is TC-5 / CS composite material, the blue line is TC-10 / CS composite material, and the purple line is pure Ti3C2 powder.

[0025] Figure 6 This is the cyclic regeneration capacity of TC-5 / CS composite materials in seawater (reaction conditions: 300W Xe lamp, 0.03g TC-5 / CS, 50mL seawater, pH=7, 20℃, 1h);

[0026] Figure 7 (a) UV-vis (Ahν) for samples Co9S8 and TC-5 / CS photocatalytic materials 1 / 2 vs (hν) curve; (b) Effect of different free radical scavengers on the photogenerated H2O2 yield (reaction conditions: 300WXe lamp, 0.05g TC-5 / CS, 50mL H2O, pH = 9, 10℃); (c) ·OH and ·O2 - Free radical capture ESR detection spectrum. DETAILED DESCRIPTION

[0027] Specific implementation method 1: The preparation method of the Ti3C2 / Co9S8 heterojunction photocatalytic material in this implementation method is implemented according to the following steps:

[0028] 1. Preparation of Co9S8 matrix:

[0029] Dissolve Co(NO3)2·6H2O in deionized water, stir to obtain a cobalt nitrate solution, then add CH3CSNH2 and NaOH to the cobalt nitrate solution in sequence, stir and mix at room temperature for 1.5 to 3 hours, wash the solid phase product with water, and dry to obtain a Co9S8(CS) matrix;

[0030] 2. Preparation of Ti3C2:

[0031] a. Add titanium aluminum carbide (Ti3AlC2) to a 40wt.% hydrofluoric acid solution, stir and react for 45 to 60 hours at room temperature, and wash and dry the solid phase to obtain a precursor Ti3C2 powder;

[0032] b. Dispersing the precursor Ti3C2 powder in a dimethyl sulfoxide (DMSO) solution, stirring for 20 to 30 hours, and then ultrasonically treating for 1 to 2 hours, and obtaining Ti3C2 powder after washing and drying;

[0033] 3. Preparation of Ti3C2 / Co9S8 heterojunction photocatalytic materials:

[0034] The Co9S8 matrix and Ti3C2 powder are mixed and ground to obtain a mixed powder, which is dispersed in DMSO and stirred at room temperature for 20 to 30 hours, then ultrasonically treated for 1 to 2 hours, and the reaction product is washed and dried to obtain a Ti3C2 / Co9S8 heterojunction photocatalytic material.

[0035] In this embodiment, Ti3C2 is composited with a narrow-bandgap n-type semiconductor material Co9S8 matrix to form a heterojunction catalyst, which expands the absorption range of sunlight, promotes the separation of photoinduced electrons and holes, and improves the photocatalytic performance.

[0036] The preparation method of the Ti3C2 / Co9S8 heterojunction photocatalytic material in this embodiment includes the following beneficial effects:

[0037] 1. The Ti3C2 / Co9S8 heterojunction photocatalytic material prepared in this embodiment uses the transition metal sulfide semiconductor material Co9S8 as the matrix and constructs an S-type heterostructure with the Mxenes material Ti2C3, so that the advantages of different materials are combined to form a synergistic effect, which enhances the material's ability to absorb light, expands the visible light response range of the photocatalytic reaction, promotes the separation of photogenerated electrons and holes, and inhibits the recombination of photogenerated carriers. By reasonably designing the interface structure and regulating the electron transmission path, the selectivity and yield of H2O2 are effectively improved, and the catalyst can be reused for more than 5 times.

[0038] 2. The Ti3C2 / Co9S8 heterojunction photocatalytic material prepared in this embodiment does not use pure oxygen and electron proton donors in the photo-production of H2O2, which reduces the demand for external oxygen sources and electron donors and improves the sustainability and economy of the reaction. The O2 dissolved in water is effectively utilized throughout the process, and is replenished by the O2 generated during the reaction. The H2O2 yield is the same as whether pure O2 is used; the H2O2 yield under the action of the S-type heterojunction catalyst is similar to the yield value of the catalytic system of other catalysts under the same conditions when electron and proton donors are introduced, that is, relying on the synergistic effect of its own photogenerated carriers can also promote the photocatalytic reaction and improve the reaction efficiency and selectivity.

[0039] 3. This embodiment prepares Ti3C2 / Co9S8 heterojunction photocatalytic materials, and photocatalytically produces H2O2 from seawater instead of pure water, which can reduce dependence on freshwater resources and reduce production and storage costs. Traditional photocatalysts are easily interfered by salt, organic matter and other impurities in seawater environments. Heterojunction photocatalysts effectively utilize the 3.0-5.0% salt content in seawater and increase the H2O2 yield.

[0040] 4. The method for preparing the Ti3C2 / Co9S8 heterojunction photocatalytic material in this embodiment has the characteristics of simple process, easy operation and low equipment requirements.

[0041] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that the concentration of the cobalt nitrate solution in step 1 is 0.02-0.03 g / mL.

[0042] Specific implementation method three: The difference between this implementation method and specific implementation method one or two is that in step one, 2.5-3.5 g Co(NO3)2·6H2O is dissolved in 140-160 mL deionized water, stirred to obtain a cobalt nitrate solution, and then 2.8-3.2 g CH3CSNH2 and 2-2.4 g NaOH are added to the cobalt nitrate solution in sequence.

[0043] Specific embodiment 4: This embodiment is different from specific embodiments 1 to 3 in that the solid phase product in step 1 is dried at 50° C. for 20 to 26 hours after being washed with water.

[0044] Specific implementation mode 5: This implementation mode is different from specific implementation modes 1 to 4 in that the washing in step a of step 2 is carried out by sequentially using water and anhydrous ethanol for sufficient washing.

[0045] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that in step 2, aluminum titanium carbide is added to a hydrofluoric acid solution with a concentration of 40 wt.%, and the mass volume ratio of aluminum titanium carbide to the hydrofluoric acid solution is controlled to be 1 g:20 mL.

[0046] Specific embodiment 7: This embodiment is different from any one of specific embodiments 1 to 6 in that the stirring time in step b in step 2 is 22 to 26 hours, followed by ultrasonic treatment for 1 hour.

[0047] Specific embodiment eight: This embodiment differs from any one of specific embodiments one to seven in that in step three, Co9S8 matrix and Ti3C2 powder are mixed in a mass ratio of (2.8-3.2): (0.14-0.16).

[0048] Specific embodiment 9: This embodiment is different from specific embodiments 1 to 8 in that in step 3, the mixed powder is dispersed in DMSO, stirred at room temperature for 22 to 26 hours, and then ultrasonically treated for 1 hour.

[0049] Specific embodiment ten: This embodiment is different from any one of specific embodiments one to nine in that the content of Ti3C2 in the Ti3C2 / Co9S8 heterojunction photocatalytic material in step three is 5wt%.

[0050] This embodiment regulates the content of Ti3C2 in the Ti3C2 / Co9S8 heterojunction photocatalytic material. Co9S8 nanosheets loaded with an appropriate amount of Ti3C2 can most effectively separate photogenerated charges and promote electron transfer of the composite material, thereby having a higher photocatalytic H2O2 production activity.

[0051] Example 1: The preparation method of the Ti3C2-5 / Co9S8 heterojunction photocatalytic material of this example is implemented according to the following steps:

[0052] 1. Preparation of Co9S8 matrix:

[0053] 3.0 g of Co(NO3)2·6H2O was dissolved in 150 mL of deionized water and stirred to obtain a cobalt nitrate solution. Then 3.09 g of CH3CSNH2 and 2.2 g of NaOH were added to the cobalt nitrate solution in sequence and stirred at room temperature for 2 h. The solid phase product was washed with water and dried (dried at 50 ° C for 24 h) to obtain a black Co9S8(CS) matrix.

[0054] 2. Preparation of Ti3C2:

[0055] a. Add 1 g of titanium aluminum carbide (Ti3AlC2) into 20 mL of a 40 wt.% hydrofluoric acid solution, stir and react at room temperature for 48 h, separate the solid phase by centrifugation, and then wash it thoroughly with water and anhydrous ethanol, and finally dry it at 60 ° C for 8 h to obtain a precursor Ti3C2 powder;

[0056] b. Disperse the precursor Ti3C2 powder in 30 mL of dimethyl sulfoxide (DMSO) solution, stir for 24 h, and then ultrasonically treat for 1 h to promote Ti3C2 delamination under ultrasonic conditions. Wash thoroughly with water and anhydrous ethanol, and dry to obtain Ti3C2 powder.

[0057] 3. Preparation of Ti3C2-5 / Co9S8 heterojunction photocatalytic materials:

[0058] 3 g of Co9S8 matrix and 0.158 g of Ti3C2 powder were mixed and ground to obtain a mixed powder. The mixed powder was dispersed in 25 mL of DMSO and stirred at room temperature for 24 h, then ultrasonically treated for 1 h. The reaction product was washed three times with water and ethanol and dried (50 ° C for 24 h) to obtain Ti3C2-5 / Co9S8 heterojunction photocatalytic material (i.e., the content of Ti3C2 in the Ti3C2 / Co9S8 heterojunction photocatalytic material is 5 wt%).

[0059] Example 2: The difference between this example and Example 1 is that in step three, 3 g of Co9S8 matrix and 0.062 g of Ti3C2 powder are mixed and ground to obtain a mixed powder, which is dispersed in 25 mL of DMSO and stirred at room temperature for 24 h to obtain Ti3C2-2 / Co9S8 heterojunction photocatalytic material. The other steps and parameters are the same as those in Example 1.

[0060] Example 3: The difference between this example and Example 1 is that in step three, 3 g of Co9S8 matrix and 0.333 g of Ti3C2 powder are mixed and ground to obtain a mixed powder, which is dispersed in 25 mL of DMSO and stirred at room temperature for 24 h to obtain Ti3C2-10 / Co9S8 heterojunction photocatalytic material. The other steps and parameters are the same as those in Example 1.

[0061] Example 4: This example uses only black Co9S8 powder.

[0062] Example 5: This example uses only Ti3C2 powder.

[0063] The present invention will be further described below in conjunction with the accompanying drawings and embodiments:

[0064] like Figure 1As shown, the typical XRD patterns of different Ti3C2 contents in the comparative sample Ti3C2 / Co9S8 composite material at 5°-70°. In the figure, the black line is Co9S8 prepared in step 1 of Example 1, the pink line is Ti3C2-5 / Co9S8 (TC-5 / CS) prepared in Example 1, the green line is Ti3C2-2 / Co9S8 (TC-2 / CS) prepared in Example 2, the blue line is Ti3C2-10 / Co9S8 (TC-10 / CS) prepared in Example 3, and the purple line is Ti3C2 material prepared in step 2 of Example 1;

[0065] from Figure 1 It can be seen that the positions of the XRD diffraction peaks of Co9S8 that can be identified in the spectrum are located at 2θ=16.8°, 29.7°, 31.2°, 47.5° and 52.3°, respectively. Compared with the standard spectrum (PDF#03-0631), they match the (111), (311), (222), (511) and (440) crystal planes respectively. The Co9S8 phase peak of the sample Ti3C2 / Co9S8 is weaker than the diffraction peak of pure Co9S8, which is due to the covering effect of the Co9S8 layer embedded in the Ti3C2 material. Pure Ti3C2 has diffraction peaks at 2θ=8.5°, 18.2°, 27.5°, 35.2°, 42.1° and 61.4°, which correspond to the (002), (006), (008), (001), (012) and (110) crystal planes of Ti3C2, respectively, according to the standard spectrum (PDF: 00-131-1400). Samples TC-x / CS all have typical diffraction peaks of Ti3C2, indicating that the Ti3C2 phase forms an interface structure in the Co9S8 matrix. With the increase of Ti3C2 content, the purity of Co9S8 decreases, and the intensity of the Co9S8 diffraction peak of sample TC-x / CS weakens. Co9S8 nanosheets are affected by the layered structure of Ti3C2, and the tendency of forming Ti3C2 / Co9S8 heterojunctions between them increases. However, after being modified by Ti3C2, Co9S8 still maintains a good self-structure.

[0066] like Figure 2 As shown, the composition diagram and SEM photos of Co9S8 and Ti3C2-5 / Co9S8;

[0067] from Figure 2 It can be seen that the SEM photos clearly show that the Co9S8 matrix is ​​in the form of aggregated nano-flower ball clusters; after the introduction of Ti3C2 into the matrix, irregular layered structures of Co9S8 nanosheets are distributed in the sheet intercalation. The Co9S8 nanosheets are directly embedded between the "sheets" of Ti3C2, and there is a tightly bound overlapping area between the two phases, which further provides a basis for the successful intercalation.

[0068] like Figure 3 As shown, the transient photocurrent response diagrams of the samples Co9S8 and Ti3C2 / Co9S8. In the figure, the black line represents the sample Co9S8, the purple line represents the sample Ti3C2, the red line represents TC-5 / CS prepared in Example 1, the green line represents TC-2 / CS prepared in Example 2, and the blue line represents the transient photocurrent response diagram of TC-10 / CS prepared in Example 3;

[0069] From Figure 3 it can be seen that the transient photocurrent response intensities are in the order of Ti3C2 < Co9S8 < TC-10 / CS < TC-2 / CS < TC-5 / CS, indicating that the introduction of Ti3C2 into the Co9S8 matrix can improve the photogenerated electron transport ability of the matrix nanosheets. The transient photocurrent response of TC-5 / CS is higher than that of the other 4 samples, indicating that an appropriate Ti3C2 content promotes the electron transport ability of the TC-x / CS composite materials.

[0070] As Figure 4 shown, the Nyquist curve diagrams of the samples Co9S8, Ti3C2 / Co9S8, and Ti3C2. In the figure, the black line represents pure Co9S8 powder, the green line represents the TC-2 / CS composite material, the pink line represents the TC-5 / CS composite material, the blue line represents the TC-10 / CS composite material, and the purple line represents pure Ti3C2 powder;

[0071] From Figure 4 it can be clearly seen that the impedance radius of the pure Co9S8 sample is the largest. After the introduction of Ti3C2 into the Co9S8 matrix, the impedance radius decreases significantly until the loading amount reaches 10 wt.%. The Co9S8 nanosheets loaded with an appropriate amount of Ti3C2 can most effectively separate photogenerated charges and promote the electron transfer of the composite material, while the overloaded Ti3C2 increases the resistance to the separation of e - -h + pairs. This result also agrees with the Figure 3 conclusion.

[0072] As Figure 5 shown, the effect of the Ti3C2 content of the samples Co9S8, Ti3C2 / Co9S8, and Ti3C2 on the H2O2 production rate in pure water and seawater (reaction conditions: 300W Xe lamp, 0.03g photocatalyst, 50mL pure water, pH = 7, 20°C). In the figure, the black line represents pure Co9S8 powder, the green line represents the TC-2 / CS composite material, the pink line represents the TC-5 / CS composite material, the blue line represents the TC-10 / CS composite material, and the purple line represents pure Ti3C2 powder;

[0073] From Figure 5It can be seen that the H2O2 production of samples TC-2 / CS, TC-5 / CS, and TC-10 / CS in pure water after 2h of photoreaction can reach 5.62mM·h -1 ·g cat -1 , 7.40 mM·h -1 ·g cat -1 and 5.61 mM·h -1 ·g cat -1 In the TC-5 / CS structure, Ti3C2 and the matrix material are dispersed more evenly, and have higher photoelectron transport, carrier density and e - -h + The composite inhibition ability is good, and a good synergistic effect is obtained in the photocatalytic process, effectively achieving the highest H2O2 yield in the sample. The H2O2 yield of the sample TC-x / CS in seawater is significantly improved compared with pure water. After TC-x / CS forms a heterojunction, it produces a good synergistic effect with specific ions in seawater, which increases the H2O2 yield. TC-5 / CS can achieve a H2O2 yield of 12.48mM·h within 2h. -1 ·gcat -1 , which is 1.69 times that of pure water.

[0074] like Figure 6 As shown, the cyclic regeneration ability of TC-5 / CS composite materials in seawater (reaction conditions: 300W Xe lamp, 0.03g TC-5 / CS, 50mL seawater, pH=7, 20℃, 1h);

[0075] from Figure 6 It can be seen that after the deactivated photocatalyst is treated with a mixed solution of CH3CSNH2 and NaOH, the treated photocatalyst can be reused for more than 5 times, and the H2O2 yield does not decrease significantly.

[0076] like Figure 7 As shown, the sample Co9S8 and TC-5 / CS photocatalytic materials (a) UV-vis (Ahν) 1 / 2 vs (hν) curve; (b) the effect of different free radical scavengers on the photogenerated H2O2 yield (reaction conditions: 300W Xe lamp, 0.05g TC-5 / CS, 50mLH2O, pH = 9, 10℃); (c) ·OH and ·O2 - Free radical capture ESR detection spectrum;

[0077] from Figure 7 As can be seen from the figure, the E VB and E CB The calculated values ​​are 1.61 eV and -0.37 eV, respectively. - The presence of the trapping agent DMSO severely reduced the yield of H2O2, confirming that e- It is the main active species for the two-electron reduction of O2 to produce H2O2. Strong DMPO-·O2 can be observed in both pure water and seawater. - The signal in seawater is stronger than that in pure water, and the signal of TC-5 / CS is stronger than that of pure Co9S8. The above results show that the existence of Ti3C2 intercalation helps to open up an auxiliary channel to achieve single-electron reduction of O2.

[0078] In summary: the Ti3C2-5 / Co9S8 composite material prepared in Example 1 has high photocatalytic H2O2 production activity and excellent stability, and can be used as a new material for photocatalytic preparation of H2O2.

Claims

1. A method for preparing a two-dimensional nano titanium carbide / cobalt octasulfide heterojunction photocatalytic material, characterized in that The preparation method is achieved by the following steps:

1. Preparation of Co9S8 matrix: Dissolve Co(NO3)2·6H2O in deionized water, stir to obtain a cobalt nitrate solution, then add CH3CSNH2 and NaOH to the cobalt nitrate solution in sequence, stir and mix at room temperature for 1.5 to 3 hours, wash the solid phase product with water, and dry to obtain a Co9S8 matrix; 2. Preparation of Ti3C2: a. Add aluminum titanium carbide to a 40wt.% hydrofluoric acid solution, stir and react at room temperature for 45 to 60 hours, and wash and dry the solid phase to obtain a precursor Ti3C2 powder; b. Dispersing the precursor Ti3C2 powder in a dimethyl sulfoxide solution, stirring for 20 to 30 hours, and then ultrasonically treating for 1 to 2 hours, and obtaining Ti3C2 powder after washing and drying; 3. Preparation of Ti3C2 / Co9S8 heterojunction photocatalytic materials: The Co9S8 matrix and Ti3C2 powder are mixed and ground to obtain a mixed powder, which is dispersed in DMSO and stirred at room temperature for 20 to 30 hours, then ultrasonically treated for 1 to 2 hours, and the reaction product is washed and dried to obtain a Ti3C2 / Co9S8 heterojunction photocatalytic material.

2. The method for preparing the two-dimensional nano-titanium carbide / cobalt octasulfide heterojunction photocatalytic material according to claim 1, characterized in that The concentration of the cobalt nitrate solution in step 1 is 0.02-0.03 g / mL.

3. The method for preparing the two-dimensional nano-titanium carbide / cobalt octasulfide heterojunction photocatalytic material according to claim 1, characterized in that In step 1, 2.5-3.5 g of Co(NO3)2·6H2O is dissolved in 140-160 mL of deionized water, stirred to obtain a cobalt nitrate solution, and then 2.8-3.2 g of CH3CSNH2 and 2-2.4 g of NaOH are sequentially added to the cobalt nitrate solution.

4. The method for preparing the two-dimensional nano-titanium carbide / cobalt octasulfide heterojunction photocatalytic material according to claim 1, characterized in that In step 1, the solid phase product is washed with water and then dried at 50° C. for 20 to 26 hours.

5. The method for preparing the two-dimensional nano-titanium carbide / cobalt octasulfide heterojunction photocatalytic material according to claim 1, characterized in that In step 2, aluminum titanium carbide is added to a hydrofluoric acid solution with a concentration of 40 wt.%, and the mass volume ratio of aluminum titanium carbide to the hydrofluoric acid solution is controlled to be 1 g:20 mL.

6. The method for preparing the two-dimensional nano-titanium carbide / cobalt octasulfide heterojunction photocatalytic material according to claim 1, characterized in that In step 2, the stirring time of step b is 22 to 26 hours, followed by ultrasonic treatment for 1 hour.

7. The method for preparing the two-dimensional nano-titanium carbide / cobalt octasulfide heterojunction photocatalytic material according to claim 1, characterized in that In step three, Co9S8 matrix and Ti3C2 powder are mixed in a mass ratio of (2.8-3.2): (0.14-0.16).

8. The method for preparing the two-dimensional nano-titanium carbide / cobalt octasulfide heterojunction photocatalytic material according to claim 1, characterized in that In step 3, the mixed powder is dispersed in DMSO, stirred at room temperature for 22 to 26 hours, and then ultrasonically treated for 1 hour.

9. The method for preparing the two-dimensional nano-titanium carbide / cobalt octasulfide heterojunction photocatalytic material according to claim 1, characterized in that In step three, the content of Ti3C2 in the Ti3C2 / Co9S8 heterojunction photocatalytic material is 5wt%.

10. Use of the two-dimensional nano titanium carbide / cobalt octasulfide heterojunction photocatalytic material prepared as claimed in claim 1, characterized in that The Ti3C2 / Co9S8 heterojunction photocatalytic material was applied to photocatalytic H2O production of H2O2.

Citation Information

Patent Citations

  • Preparation method of two-dimensional Z type heterojunction visible light photocatalyst

    CN109759121A

  • Preparation method of two-dimensional titanium carbide / two-dimensional graphite phase carbon nitride nanosheet heterojunction and application of heterojunction in photocatalytic reduction of CO2

    CN111215115A

  • Co9S8 / ZnIn2S4 photocatalytic hydrogen production material as well as preparation method and application thereof

    CN113751029A

  • Cobalt sulfide / titanium carbide / carbon cloth composite anode material and preparation method and application thereof

    CN118289894A

  • Titanium oxide and method for producing the same

    JP2010260760A